IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV/AIDS DI PUSKESMAS TELADAN - Suharto, Suharto; Gurning, Fitriani Pramita; Pratama, Muchti Yuda; Suprayitno, Emdat (Jurnal Riset Hesti Medan, 2019)
One of the diseases that is now considered a problem that has received enough attention from the government is HIV and AIDS. Talking about HIV and AIDS means it discusses health issues that are currently quite sensitive to talk about. This relates to the unique nature of this disease. Besides the case which is like an iceberg phenomenon, namely the spread of HIV and AIDS cases that cannot be predicted at the initial phase and also has not found a cure to cure it. The purpose of this study is to obtain in-depth data on the implementation of HIV/AIDS policies in the Model Health Center, whether the policies made by the government run well or not in the field. This research uses a qualitative research method with descriptive research type on June 28, 2019, by interviewing informants and distributing questionnaires. As for the total overall value of the Government Policy Implementation is 235. The value of the implementation of government policies, amounting to 78.33% of the 100% expected results. The overall total value of HIV and AIDS is 83. HIV/AIDS counts in the working area of the Exemplary Health Center, which is 92.22% of the 100% expected results. Conclusions policy implementation has been going well and has been socialized to the community and health services, people at risk and sufferers of  HIV/AIDS in the work area of the Community Health Center already has its own organization where this organization is expected to help achieve the goals of this HIV/AIDS program, and to achieve this goal the Community Health Center conducts activities in the form of mobile clinics where the exemplary Community Health Center goes directly to conduct examinations to the community, and in terms of treatment for patients so far it can be said to be in good category and runs smoothly but there are obstacles where sufferers continue to do things that can trigger the development of the HIV virus although in addition patients continue to take drugs to inhibit and minimize the development of the HIV virus.